Improving The Work Culture of Civil Servants Through Mental Revolution in The Ministry of Religious Affairs of Papua - Haisang Haisang (TATHO: International Journal of Islamic Thought and Sciences, 2024)
This study explores the effectiveness of the mental revolution program in improving the work culture of State Civil Apparatus in the Ministry of Religious Affairs of Papua Province. Using a qualitative approach, this study combined in-depth interviews, participant observation, and document analysis to collect data from 25 key informants. Data analysis integrated transformative learning theory, cultural intelligence model, and appreciative organisational change theory. The findings indicate a significant improvement in the work culture intelligence of the State Civil Apparatus (ASN) in the Ministry of Religious Affairs of Papua Province, especially in the metacognitive dimension, and a surprising transformation of perspective in an initially resistant group. This study expands understanding of the intersection between transformative learning, cultural intelligence, and organisational change in religious institutions. The theoretical implications include the development of a new framework for change management that is sensitive to cultural and spiritual contexts in a highly diverse region.